27.0k views
5 votes
Simplify (2xy^3)^4.
a.8xy12

b.2x4y12

c.16xy12

d.16x4y12

User Kviiri
by
6.0k points

2 Answers

3 votes

Answer:

d option 16x^4y^12)

Step-by-step explanation

Concept used: (xy)^n = x^n. y^n

Applying the concept in given equation

(2xy^3)^4

= (2)^4. (x)^4. (y^3)^4

= 16 . x^4 . y^12

= 16x^4y^12

User Itdxer
by
6.4k points
2 votes

Answer:

d 16 x^4 y^12

Explanation:

(2xy^3)^4

We know that

(ab)^c is a^c b^c

So

2^4 x^4 y^3^4

We also know that a^b^c is a^(b*c)

16 x^4 y^(3*4)

16 x^4 y^12

User Viral Narshana
by
6.1k points